Spin-controlled directional launching of surface plasmons at the subwavelength scale - 黄韬 王佳见 李梓维 刘伟 林峰 方哲宇 朱星 (Chinese physics B, 2016)
In this paper, we demonstrate a spin-controlled directional launching of surface plasmons at the subwavelength scale.Based on the principle of optical spin＇s effect for the geometric phase of light, the nanostructures were designed. The inclination of the structures decides the spin-related geometric phase and their relative positions decide the distance-related phase. Hence, the propagation direction of the generated surface plasmon polaritons（SPPs） can be controlled by the spin of photons. Numerical simulations by the finite difference time domain（FDTD） method have verified our theoretical prediction. Our structure is fabricated on the Au film by using a focused ion beam etching technique. The total size of the surface plasmon polariton（SPP） launcher is 320 nm by 180 nm. The observation of the SPP launching by using scanning near-field optical microscopy is in agreement with our theory and simulations. This result may provide a new way of spin-controlled directional launching of SPP.